Effect of different nutrient doses and POLY4 on quality and physiological parameters of mustard - Anil Jakhar; Artika Singh; Rahul Jakhar; Jhabar Singh Lochhib; Meena Nehara; Shaily Purohit (Journal of Oilseed Brassica, 2025)
A field experiment was carried out during the rabi season 2021-22 to assess the effects of POLY4 on the performance of Indian mustard (Brassica juncea L.) variety Giriraj at Rani Lakshmi Bai Central Agricultural University research farm in Jhansi. The study utilized a randomized block design with nine distinct nutrient management treatments, each replicated three times. The findings indicated that the treatment T7 , which included 100% RDF (25% K by MOP and 75% K by POLY4), resulted in significantly higher oil content, yield, nutrient uptake, and improved physiological parameters compared to other treatments.